Flocculation of protein in seafood process water, Evaluation of flocculants in the presence of high salt content - Hagström, Martin (My University, 2022)
Water is a necessity to produce marinated herring. One application of water is in the various brines used for pre-salting, marinating and maturing the herring to achieve the sought-after quality. During these processes high quality nutrients from herring inevitably leach out into the water and will subsequently be lost. Recovery of these nutrients, via food-grade flocculation, would ameliorate sustainability whilst simultaneously decrease effluent taxation cost. Flocculation was performed on two pre-salting brines (5% and 13%) from the herring industry using chitosan, alginate, carrageenan, silica, and crystal nanocellulose (CNC) as flocculants. Responses measured were relative sediment height (RSH) and protein sedimentability (%) after one hour sedimentation at room temperature. First the influence of pH on flocculation with the above-mentioned flocculants was analyzed. Flocculation with 0.45 g/L carrageenan and 0.5 g/L alginate performed the best at pH 4 in the 5% brine, while chitosan performed the best at pH 4.5. Flocculation with CNC at 0.5 g/L showed effect on the 5% brine, but no optimal pH could be determined, whilst flocculation with silica at 0.5 g/L showed no effect. None of the flocculants displayed any flocculation in the 13% brine. Secondly, the influence of the concentration of carrageenan and alginate on flocculation was investigated. Flocculation with carrageenan (0.09-0.9 g/L) at pH 4 reduced RSH the most, indicating efficient sedimentation of flocs. Optimal carrageenan concentrations were 0.675 g/L and 0.9 g/L, which yielded the greatest protein sedimentability, ~99%. Flocculation, at pH 4, with alginate (0.1-1.0 g/L) gave the second highest reduction of RSH whilst protein sedimentability reached around 98%. No specific concentration proved optimal, and rather alginate was effective over the whole concentration range. With the intention of creating two model systems for optimizing flocculation of herring brines, protein extractions of herring mince at low (0.05 M) and high (0.7M) ionic strength were done. The optimal extraction-liquid to mince ratio was 10:1 with respect protein recovery (%) and ease of use. SDS-PAGE showed enrichment of sarcoplasmic proteins in low salt extracts and of myofibrillar proteins in high salt extracts. It was concluded that optimization of flocculation would be done on the brines themselves and that artificially built model systems would be more suitable for evaluating flocculation mechanisms.
Keywords: Flocculation; Protein recovery; Food grade flocculant; Chitosan; Alginate; Carrageenan; Silica; Crystal nano cellulose; Seafood process water